Performance improvement of microLED-to-microLED visible light communication using reverse bias - Bo-Guen Kim; Sung-Man Kim (ETRI Journal)
LED-to-LED visible light communication (VLC), which uses LEDs not only for the transmitter but also for the receiver, is being studied as an efficient optical wireless communication technology that uses LED lighting infrastruc-ture. In this paper, we investigate microLED-to-LED VLC, which uses micro-LEDs as both the transmitter and receiver. In particular, we conducted a study to improve the performance of microLED-to-microLED VLC. For this, we measured the performance depending on the transmitter and receiver LED color combination. In addition, the effects of zero bias and reverse bias at the receiver LED were investigated. We also investigated the improvement in the reverse bias when applying a transimpedance amplifier to the receiver LED. Finally, we experimentally demonstrated a data rate of 360 kbps in the microLED-to-microLED VLC.